Negotiating national identity in postcolonial Zimbabwe through a national dress - Chitima, Simbarashe Shadreck (Wiley Online, 2022)
A national dress is a reflection of national consciousness towards the nation and its cultural heritage. Instead of simply being functional, a national dress is also a script that exhibits people's identities. This study examines how Zimbabweans identify with the national dress as a facet of achieving national identity. Qualitative research methods and Gramscianism were employed in the study. It is revealed that the majority of Zimbabweans fail to identify with the national dress due to political, cultural and economic reasons. The national dress is perceived as a campaign strategy being used by the state to achieve political expediency and to be seen as champion of moral as well as cultural regeneration. Some participants associate the dress with cultural imperialism and waste of resources. Very few participants take the dress as a positive step towards the decolonisation of cultural spaces and identities. Conclusively, the majority of Zimbabweans find the dress insignificant in their lives and in national identity construction.